Multimodal prediction based on ultrasound for response to neoadjuvant chemotherapy in triple negative breast cancer - Maohua Lyu; Shouheng Yi; Chunyan Li; Yu Xie; Yu Liu; Zeyan Xu; Zhitao Wei; Huan Lin; Yunlin Zheng; Chunwang Huang; Xi Lin; Zaiyi Liu; et al. (npj Precision Oncology)
Abstract Pathological complete response (pCR) can guide surgical strategy and postoperative treatments in triple-negative breast cancer (TNBC). In this study, we developed a Breast Cancer Response Prediction (BCRP) model to predict the pCR in patients with TNBC. The BCRP model integrated multi-dimensional longitudinal quantitative imaging features, clinical factors and features from the Breast Imaging Data and Reporting System (BI-RADS). Multi-dimensional longitudinal quantitative imaging features, including deep learning features and radiomics features, were extracted from multiview B-mode and colour Doppler ultrasound images before and after treatment. The BCRP model achieved the areas under the receiver operating curves (AUCs) of 0.94 [95% confidence interval (CI), 0.91–0.98] and 0.84 [95%CI, 0.75–0.92] in the training and external test cohorts, respectively. Additionally, the low BCRP score was an independent risk factor for event-free survival (P < 0.05). The BCRP model showed a promising ability in predicting response to neoadjuvant chemotherapy in TNBC, and could provide valuable information for survival.